An Alternate Process for the Solid‐Phase Synthesis and Solid‐Phase Purification of Synthetic Nucleic Acid Sequences. Issue 1 (11th January 2023) - Cawrse, Brian M.; Takahashi, Mayumi; Grajkowski, Andrzej; Beaucage, Serge L.
Abstract: The chemical synthesis of a riboside phosphoramidite has been achieved to provide a 5‐ O ‐capture linker and a 2‐ O ‐silyl ether protecting group with the intent of enabling an efficient solid‐phase purification of synthetic DNA sequences. The riboside phosphoramidite has been incorporated into a DNA sequence while performing the penultimate automated solid‐phase synthesis cycle of the sequence. The terminal 5‐ O ‐riboside moiety of the resulting DNA sequence is then conjugated to a capture linker to create an anchor for the solid‐phase purification of the DNA sequence conjugate. Release of all DNA sequences from the synthesis support is achieved under standard basic conditions to yield a mixture of the desired DNA sequence conjugate along with unconjugated, shorter‐than‐full‐length sequence contaminants. Upon exposure of all DNA sequences to a capture solid support, only the DNA sequence conjugate is chemoselectively captured, thereby allowing the unconjugated shorter‐than‐full‐length DNA sequences to be efficiently washed away from the capture support. After 2‐ O ‐cleavage of the silyl ether protecting group from the terminal riboside ethylphosphate triester conjugate, the solid‐phase‐purified DNA sequence is efficiently released from the capture support through an innovative intramolecular cyclodeesterification of the ethylphosphate triester, prompted by the riboside's rigid cis ‐diol conformer, to provide a highly pure DNA sequence. Published 2023. This article is a U.S. Government work and is in the public domain in the USA. Basic Protocol 1 : Preparation of 5‐ O ‐(4, 4′‐dimethoxytrityl)‐2‐ O ‐ tert ‐butyldimethylsilyl‐1, 4‐anhydro‐D ‐ribitol (3 ) Basic Protocol 2 : Preparation of 5‐ O ‐(4, 4′‐dimethoxytrityl)‐2‐ O ‐ tert ‐butyldimethylsilyl‐3‐ O ‐[( N, N ‐diisopropylamino)ethyloxyphosphinyl]‐1, 4‐anhydro‐D ‐ribitol (6 ). Basic Protocol 3 : Automated synthesis of the chimeric solid‐phase‐linked DNA sequence 8 . Support Protocol : Preparation of 2‐cyanoethyl‐(5‐oxohexyl)‐ N, N ‐diisopropylphosphoramidite (9 ). Basic Protocol 4 : Solid‐phase purification of the chimeric DNA sequence 10